Corruption and its Repercussions on Employment, Poverty and Inequality: Rwanda and South Africa Compared - Khan, Firoz; Pillay, Pregala (Journal of Reviews on Global Economics, 2019)
Effective statecraft is founded on governance, planning and policy execution foundations that are historically derived and conditioned. In contemporary times, effective statecraft supposedly centres on ‘sustainable' development paradigms and frameworks. This paper examines the connection between state construction and contemporary statecraft - refracted through anti-corruption policy and implementation - and their combined repercussions on employment, poverty and inequality. These include the challenges encountered by the proliferation of corruption, which many posit to be the ‘key enemy' of good governance and, by extension, ‘sustainable' development. Using Rwanda and South Africa as case studies, it is demonstrated that fighting corruption cannot be disconnected from power, political economy, the dynamics of public policy formulation, and the mechanics of policy implementation. This paper posits an association between specific types of patrimonialism, economic performance and service delivery with attendant consequences for employment generation, poverty eradication and reducing inequality.